Effect of Shewanella oneidensis MR-1 on U(VI) sequestration by montmorillonite. (February 2022) - Wang, Shuqin; Shi, Lei; Yu, Shujun; Pang, Hongwei; Qiu, Muqing; Song, Gang; Fu, Dong; Hu, Baowei; Wang, Xiangxue
Abstract: Bacteria may change the physicochemical properties of montmorillonite and further effect the disposal of high-level radioactive waste. Therefore, we explored the influence of Shewanella oneidensis MR-1 on the elimination of representative radionuclide U(VI) by montmorillonite (MMT). The batch experiments showed that MR-1 significantly enhanced the removal efficiency of U(VI), the adsorption capacity of MMT improved from 8.4 to 16.1 mg/g after addition of MR-1, and the adsorption type changed from Langmuir to Freundlich. FTIR and XPS analysis revealed that hydroxyl, phosphate, carbonyl and amine in MMT + MR-1 were primary actors in the elimination of U(VI). The U 4f high-resolution XPS spectrum of MMT + MR-1 showed U(VI) and U(IV) peaks at the same time, indicating that the adsorption process was accompanied by the reduction reaction, which may be due to the extracellular respiration of MR-1. These investigations are significant to insight the potential significance of microbial processes for the transport and elimination of U(VI) in repositories, which in return will contribute to their safe disposal. Graphical abstract: Image 1 Highlights: ● Synergetic effect existed in U(VI) sequestration onto MMT + MR-1. ● Shewanella oneidensis MR-1 enhanced the elimination of U(VI) on montmorillonite. ● The adsorbed U(VI) can be reduced to U(IV) by Shewanella oneidensis MR-1. ● The main mechanisms between U(VI) and MMT + MR-1 were adsorption and reduction.